THE INFLUENCE OF EDUCATIONAL VIDEOS ON SEXUAL VIOLENCE KNOWLEDGE IN BENGKULU PUBLIC ELEMENTARY SCHOOLS IN BENGKULU CITY 2021 - Mardiani Mardiani; Hermansyah Hermansyah; Husni Husni (Poltekkes Kemenkes Bengkulu, 2022)
Cases of sexual violence are ranked first in cases of violence against children. The Indonesian Child Protection Commission (KPAI) stated that from 2011-2016 there were 1,875 cases of sexual violence in early childhood. This study aimed to determine the effect of educational videos on the knowledge of elementary school children about sexual violence in the State of Bengkulu City in 2021.This research is quasi-experimental. The sample size of 60 students for each of the 30 intervention groups and 30 control groups. Analysis using Mann Whitney. The results showed that the average knowledge before intervention in the intervention group was 9.70 and in the control group was 10.73. The average knowledge after intervention in the intervention group was 13.93 and in the control group was 10.80. The analysis showed a significant difference in increasing the average value about maturation after marriage knowledge between groups before and after the intervention with a p value of 0.000. Thus, it is necessary to develop learning and educational methods, to increase health promotion activities, to increase the knowledge of elementary school children about sexual violence